2017
DOI: 10.1007/s10851-017-0732-6
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Non-local Total Variation and Application in Image Restoration

Abstract: In the usual non-local variational models, such as the non-local total variations (NLTV), the image is regularized by minimizing an energy term that penalizes gray-levels discrepancy between some specified pairs of pixels, a weight value is computed between these two pixels to penalize their dissimilarity. In this paper, we impose some regularity to those weight values. More precisely, we minimize a function involving a regularization term, analogous to an H 1 term, on weights. Doing so, the finite differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…In this case, we consider u = (u R , u G , u B ), M = 3 and e ∈ R |E| common to the three components of u. We compare the proposed method with state-of-the-art approaches, including "ROF" minimization [23,24], the "MS relaxation" proposed in [27], the "Discrete AT" formulation [29] and the "NL-ROF" [28], although it is not designed for RGB-color images. Since the ROF minimization and the "NL-ROF" do not allow us to directly extract the contours, we compute them by thresholding the gradient of the estimate following [23,24].…”
Section: Color Denoising and Comparisons With State-of-the-art Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, we consider u = (u R , u G , u B ), M = 3 and e ∈ R |E| common to the three components of u. We compare the proposed method with state-of-the-art approaches, including "ROF" minimization [23,24], the "MS relaxation" proposed in [27], the "Discrete AT" formulation [29] and the "NL-ROF" [28], although it is not designed for RGB-color images. Since the ROF minimization and the "NL-ROF" do not allow us to directly extract the contours, we compute them by thresholding the gradient of the estimate following [23,24].…”
Section: Color Denoising and Comparisons With State-of-the-art Methodsmentioning
confidence: 99%
“…Experiments show that this ROF-like coupling term is more robust to image gradients, but eliminates high-frequency content. More recently, Li et al [28] suggested to set e p = {e We can remark that, when dealing with multivariate images, contours can be defined either as similar edges through all the components, or as distinct edges, leading to a path K that may be different for all the components. In order to facilitate the understanding and the reading, we formulate Problem 1 in the context of similar edges.…”
Section: Generalized Discrete Mumford-shah Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8] a finite element implementation of the AT functional was proposed, refining and realigning the meshing locally around the discontinuities but extremely costly for large images. Li et al proposed in [9] a functional similar to AT functional, where (4) is approximated with a quadratic penalization. The convergence is proved but it does not perform contour detection.…”
Section: Introductionmentioning
confidence: 99%
“…Context In this paper, we are interested in the discrete formulation of Total Variation (TV) in image processing and computer vision as a prior for piecewise constant images. This topic has been widely studied since it has been proposed by Rudin-Osher-Fatemi (ROF) [3] and remains an active research field; as an example, non-local formulations have been proposed in [4], [5] and a combination of TV with Non-Local means has been proposed in [6], all in order to preserve textures and thin structures. The Total-Generalized-Variation (TGV) studied in [7] and the method in [8] are variants that reduce the staircasing effect observed with TV.…”
Section: Introductionmentioning
confidence: 99%